2010
DOI: 10.1016/j.talanta.2010.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric and voltammetric polymer lab chip sensors for determination of nitrate, pH and Cd(II) in water

Abstract: Due to their toxicity to humans and animals, heavy metals and nitrate in groundwater are of particular concern. The combination of high toxicity and widespread occurrence has created a pressing need for effective monitoring and measurement of nitrate and heavy metals in soil pore water and groundwater at shallow depths. In this work, a new electrochemical sensing platform with the self-assembly nanobeads packed (nBP) hetero columns has been developed for the pH and nitrate measurements. In addition, for on-sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…A polymer master mold containing microchannels was fabricated using a previously developed method in our lab. 19,20 Using a patterned transparency film mask, a commercially available printing press plate with a 1.05 mm thick photosensitive polymer (WA210, Flint Group, OH) was exposed to diffuse ultraviolet (UV) light (1 J/cm 2 , 365 nm). Then, the exposed printing plate was developed FIG.…”
Section: Methodsmentioning
confidence: 99%
“…A polymer master mold containing microchannels was fabricated using a previously developed method in our lab. 19,20 Using a patterned transparency film mask, a commercially available printing press plate with a 1.05 mm thick photosensitive polymer (WA210, Flint Group, OH) was exposed to diffuse ultraviolet (UV) light (1 J/cm 2 , 365 nm). Then, the exposed printing plate was developed FIG.…”
Section: Methodsmentioning
confidence: 99%
“…The second device was an adaptation to detect Cd(II). 11 The device has a similar aspect to the one previously described, but has just two groups of three electrodes. LOD was 9.3 ppb, using deposition at 21.2 V for 90 s, and detection between 21.2 and 20.5 V. The authors evaluated Pb(II) interference and observed that the peak current is 20.85 and 20.58 V for Cd (II) and Pb(II), respectively.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…This change in paradigm can be exemplified by examining the works of Ahn's group. [9][10][11][12][13] Their first paper presented a disposable heavy metal detector, but three years later they published an FDS for the same application, using similar strategies.…”
Section: Introductionmentioning
confidence: 99%
“…This solution was sealed and stored at -20 °C. 52 Nanocomposite of POT-MoS2: The weight ratio of POT to MoS2 was varied from 1:1 to 1:10 to study the influence of material composition on the redox properties of different POT-MoS2 nanocomposites. In each case, the concentration of POT solution was fixed at 2.6 mg/mL.…”
Section: Introductionmentioning
confidence: 99%